Global ecological politics - Leonard, Liam.; Barry, John, 1966- (Bingley, U.K. : Emerald, 2010)
"Advances in Ecopolitics Series" presents a collection of environmental alternatives worthy of consideration in light of the ongoing economic downturn which has accompanied the latest incarnation of unsustainable practices. Each publication discusses a significant element in the environmental theory which now represents an important aspect of sustainable living. The latest volume, "Global Ecological Politics", examines the range of environmental campaigns that are occurring across the planet. It showcases a selection of case studies on grassroots initiatives and activism in areas such as green economic alternatives, regional activism in defence of communities, alternative or utopian communities, green politics and ecotourism. This extensive array of ecological participation demonstrates that viable green alternatives are available in this current era of legitimation crisis across the formal political and economic sectors. "Global Ecological Politics" presents an important collection of articles for researchers, lecturers and academics in the socio-economic and political sector and is essential reading for those involved in all areas of environmentalism.
ch. 1. Introduction : the background to global ecopolitics / Liam Leonard -- ch. 2. The green new deal : restoring balance and stability to the global financial ecosystem / Anne Pettifor -- ch. 3. The dilemma of justice : foreign oil multinationals and human rights violation in the Niger delta of Nigeria / Victor Ojakorotu -- ch. 4. Alternative currency networks as utopian practice / Peter North -- ch. 5. Elusive escapes? : everyday life and ectopias / Jon Anderson -- ch. 6. Towards a model of green political economy : from ecological modernisation to economic security / John Barry -- ch. 7. Green politics and anthropology / Michael O'Kane -- ch. 8. Environmental disputes in France / Darren MaCauley -- ch. 9. Ecotourism and sustainability in the tourism sector / James Hanrahan -- ch. 10. The politics of waste, consumption and sustainability in the Republic of Ireland / Honor Fagan.
Keywords: Political Science -- Public Policy -- Environmental Policy; Nature -- Environmental Conservation & Protection; Environmentalist thought & ideology; Environmentalist, conservationist & Green organizations; Environmentalism